PENERAPAN ARSITEKTUR BIOFILIK PADA PERANCANGAN GREEN COWORKING SPACE DI PATI - Lina Nugraheni (Jurnal Arsitektur ARCADE, 2024)
Abstract: Coworking Space in general is a new breakthrough for an office which carries the concept of joint work and collaboration. The need for work space with the concept of collaboration, fun and affordable rental costs arises because many creative industries such as MSMEs, startup businesses, remote workers and freelance jobs are in need, especially after going through the pandemic, several jobs have emerged that do not require working in the office. Biophilic design, which incorporates natural elements into the built environment, has become a concern in efforts to improve the well-being and productivity of workspace occupants. However, research on the application of biophilic design, especially in the context of co-working spaces, is still limited. Therefore, this research aims to explore how to apply the principles of biophilic design using the 14 elements of biophilic design guidelines so that it can increase the productivity of co-working space users. The research results show that the application of biophilic design positively influences the productivity of co-working space users. Sufficient natural lighting improves concentration and working mood, while natural views such as vertical gardens can provide a fresh and calming feeling. In addition, the use of natural materials such as wood and live plants provides a friendly and inviting atmosphere for collaboration. Thus, this research concludes that the application of biophilic design in co-working spaces can help increase user productivity by creating a healthy, inspiring and sustainable environment.Keywords: Coworking Space, Biophilic Architecture, User productivityAbstrak: Coworking Space secara umum merupakan terobosan baru sebuah kantor yang didalamnya mengusung konsep kerja bersama dan kolaborasi. Kebutuhan atas ruang kerja dengan konsep kolaborasi, fun dan biaya sewa yang terjangkau muncul karena banyak industri kreatif seperti UMKM, bisnis startup, remote workers dan freelance job yang membutuhkan terlebih setelah melewati masa pandemi muncul beberapa pekerjaan yang tidak mengharuskan bekerja di kantor. Biophilic design, yang memasukkan unsur-unsur alam ke dalam lingkungan binaan, telah menjadi perhatian dalam upaya meningkatkan kesejahteraan dan produktivitas penghuni ruang kerja. Namun, penelitian tentang penerapan biophilic design khususnya dalam konteks co-working space masih terbatas. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi bagaimana penerapan prinsip biophilic design dengan menggunakan pedoman 14 elemen biophilic design sehingga dapat meningkatkan produktifitas pengguna co-working space. Hasil penelitian menunjukkan bahwa penerapan biophilic design secara positif memengaruhi produktifitas pengguna co-working space. Pencahayaan alami yang cukup meningkatkan konsentrasi dan mood kerja, sementara pemandangan alam seperti taman vertikal mampu memberikan rasa segar dan menenangkan. Selain itu, penggunaan material alami seperti kayu dan tanaman hidup memberikan nuansa yang ramah dan mengundang untuk berkolaborasi. Dengan demikian, penelitian ini menyimpulkan bahwa penerapan biophilic design dalam co-working space dapat membantu meningkatkan produktivitas pengguna dengan menciptakan lingkungan yang menyehatkan, inspiratif, dan berkelanjutan.Kata kunci: Coworking Space, Arsitektur Biofilik, Produktifitas penggunaKataÂ